2007
DOI: 10.1111/j.1750-3841.2007.00542.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Cultural Comparisons among the Sensory Characteristics of Fermented Soybean Using Korean and Japanese Descriptive Analysis Panels

Abstract: One of the most important initial steps in exporting a food product to another country from the R&D perspective is to describe and translate the sensory characteristics of a food product appropriately into the language of the target country. The objectives of this study were to describe and compare the sensory characteristics of Korean and Japanese style fermented soybean products, and to cross-culturally compare the lexicons of the identical product generated by the Korean and Japanese panelists. Four types o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 23 publications
(40 reference statements)
1
62
0
1
Order By: Relevance
“…Similarly, the American panel used original attributes, including roasted corn, nuts, red wine, and pumpkin. It has been observed in other cross-cultural studies that panelists choose peculiar descriptors drawn from their personal experiences to describe the unfamiliar sensory characteristics of a foreign product (18,25) and sometimes use idiosyncratic words that relate to personal experiences when a stimulus is unfamiliar (2). Result of the MFA on the set of samples: MFA was applied to the descriptive analysis data from the Korean, Chinese, and American panels to delineate the associations between perilla oil samples and their sensory characteristics.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, the American panel used original attributes, including roasted corn, nuts, red wine, and pumpkin. It has been observed in other cross-cultural studies that panelists choose peculiar descriptors drawn from their personal experiences to describe the unfamiliar sensory characteristics of a foreign product (18,25) and sometimes use idiosyncratic words that relate to personal experiences when a stimulus is unfamiliar (2). Result of the MFA on the set of samples: MFA was applied to the descriptive analysis data from the Korean, Chinese, and American panels to delineate the associations between perilla oil samples and their sensory characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 7 solutions were presented, with spring water used once as a control. The panelists were allowed to continue participation in the study if they identified more than 60% of the solutions correctly (18). Four panelists in total (1 Korean, 2 Chinese, and 1 American) were removed from the study at the end of the training period due to poor performance.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it is essential for food developers to understand how the consumers of a target export country perceive and describe the sensory characteristics of the product (14). In this context, interest in cross-cultural sensory studies has grown in recent years (15,16), and a number of studies have compared the sensory profiles of different cultures in European, American (17)(18)(19), and Asian countries (20,21).…”
Section: Introductionmentioning
confidence: 99%